Gardner's multiple intelligence profiles as predictors of VAK learning style preferences in indonesian catholic secondary education - Mimpin Sembiring; Thomas Tarigan; Monika br Ginting; Mudhar Mudhar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study examined Gardner's multiple intelligences theory as a predictor framework for Visual-Auditory-Kinesthetic (VAK) learning style preferences among Grade X students at Sekolah Menengah Agama Katolik Negeri Samosir, North Sumatra. Using total sampling, all 47 students enrolled during the 2024/2025 academic year participated in this quantitative correlational study. Data were collected via the Multiple Intelligences Developmental Assessment Scales (MIDAS; 80 items, 10 per subscale; Cronbach's and a VAK Learning Style Inventory (42 items: 13 visual, 15 auditory, 14 kinesthetic. Both instruments demonstrated construct validity via Confirmatory Factor Analysis. Post- hoc power analysis confirmed sample adequacy, substantially exceeding the large-effect threshold. Pearson correlation revealed a very strong overall association between intelligence profiles and learning styles. Simultaneous multiple linear regression (Enter method, all eight intelligence subscales) demonstrated that visual learning style was independently predicted by visual-spatial, logical- mathematical, and intrapersonal intelligence; auditory learning style by linguistic, musical, and interpersonal intelligence; and kinesthetic learning style by bodily-kinesthetic and naturalistic intelligence. These findings provide an empirical foundation for developing intelligence-matched differentiated instruction in Catholic secondary education, pending replication with larger and more diverse samples.